Letter from James Curtis Booth to John Sherman - Booth, James Curtis (1879)
James Curtis Booth (1810-1888) writes to the United States Secretary of the Treasury, John Sherman (1823-1900), in support of Robert E. Preston (1836-1911) as the next Director of the Mint.
Keywords: Booth, James Curtis, 1810-1888; Sherman, John, 1823-1900; United States Mint; Mint of the United States; United States. Department of the Treasury; Preston, Robert E., 1836–1911